2020
DOI: 10.7202/1066636ar
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-linguistic patterns of degree completion in BC universities: How important are high-school academic achievement and institution of entry?

Abstract: We examine bachelor's degree completion in the British Columbia post-secondary system, which is noted for its multiple pathways to graduation and ethnically diverse student population. Employing an administrative longitudinal dataset, we compare how the probability of degree completion by students enrolled at research-intensive, teaching-intensive, and college-technical institutions differs by ethno-linguistic background and high school grades. Estimates from multi-level logistic regression modelsdemonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Unfortunately, research shows that they are falling behind in provincial achievement tests when compared to their native-English-speaking counterparts (e.g., Pavlov, 2015;Roessingh & Douglas, 2012;Roessingh & Elgie, 2009). High school drop-out rates and academic failure of these students are also among the highest (e.g., Roessingh, 2004;Sweet et al, 2019;Toohey & Derwing, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, research shows that they are falling behind in provincial achievement tests when compared to their native-English-speaking counterparts (e.g., Pavlov, 2015;Roessingh & Douglas, 2012;Roessingh & Elgie, 2009). High school drop-out rates and academic failure of these students are also among the highest (e.g., Roessingh, 2004;Sweet et al, 2019;Toohey & Derwing, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that, unfortunately, ELLs in Canadian schools are falling behind in provincial achievement tests when compared to their native-English-speaking counterparts (e.g., Pavlov, 2015). The high-school dropout rates and academic failure of these students are also among the highest (e.g., Sweet et al, 2019). Cutler and Graham (2008) found that children who did not learn to write well were at a disadvantage.…”
mentioning
confidence: 99%